Challenges in The Diagnosis of Ischemic stroke, Tuberculous Meningitis, and Co-Infection with HIV in a Socially Isolated Elderly Patient - Han-Ke Huang; Chieh-Sen Chuang (Acta Neurologica Taiwanica)
Background: Ischemic stroke has been a common cause of death and disability in Taiwan, particularly among the elderly. Social isolation is a significant issue in an aging society, which can be associated with delayed medical care and difficulties in diagnosis. Case: A 76-year-old man presented with altered mental status, left-sided weakness, and declining cognitive function over three months. He had limited social connections and an unknown medical history. Initial brain imaging showed communicating hydrocephalus. Cerebrospinal fluid analysis revealed increased lymphocytes and high protein levels. Further imaging revealed multiple hyperintense lesions in the brain’s white matter and acute ischemic stroke in specific areas. The patient was diagnosed with tuberculosis and HIV coinfection, leading to probable tuberculous meningitis, HIV encephalopathy, and pneumocystis jirovecii pneumonia. Treatment with antituberculous agents, antibiotics, and steroids improved the patient’s level of consciousness. Conclusion: Addressing social isolation and altered consciousness in elderly individuals requires a thoughtful approach. Reconsidering the differential diagnosis is crucial when it doesn’t match the clinical severity. Clinicians should consider rare co-occurrences like ischemic stroke, TBM, and HIV infection in atypical TBM cases. A biopsychosocial perspective helps gather a comprehensive medical history for holistic care. Early diagnosis and timely intervention are vital for better outcomes in severe infections.